The influence of football as a ‘soft power’ in the contemporary socio-cultural situation - Kaverina, E.A.; Puyu, Yu.V.; Glinternik, E.M.; Nikonov, S.B. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to understand the phenomenon of football from the point of view of philosophical teaching and to identify the phenomenological features of football. Methods and structure of the study. In this study, the methods of theoretical and systematic analysis, including observation, were used. Results and conclusions. The philosophical study of football will allow us to get closer to the answer, since it discovers and reveals many layers in the phenomenon of football: ontological (being-in-the-game, time and space on the field), existential (freedom of choice, authenticity, absurdity and meaning), phenomenological (the player’s bodily experience, experiencing the moment), socio-philosophical (collective, leadership, identity, value, tradition, common history), aesthetic (beauty, play as art). Football appears as a rich metaphor of life: an arena where cooperation and rivalry are played out, where there are tragedies of defeats and epic victories, where everyone can find their place in the team and their personal value. Note that the study consists of two parts. The proposed first part introduces the stated issues, the second part of the article, which will be published later, discusses the main issues.